GAS6/TAM Pathway Signaling in Hemostasis and Thrombosis - Law, Luke A.; Graham, Douglas K.; Di Paola, Jorge; Branchford, Brian R. (Frontiers in Medicine, 2018)
The GAS6/TYRO3-AXL-MERTK (TAM) signaling pathway is essential for full and sustained platelet activation, as well as thrombus stabilization. Inhibition of this pathway decreases platelet aggregation, shape change, clot retraction, aggregate formation under flow conditions, and surface expression of activation markers. Transgenic mice deficient in GAS6, or any of the TAM family of receptors that engage this ligand, exhibit in vivo protection against arterial and venous thrombosis but do not show either spontaneous or prolonged bleeding compared to their wild-type counterparts. Comparable results are observed in wild-type mice treated with pharmacological inhibitors of the GAS6-TAM pathway. Thus, GAS6/TAM inhibition offers an attractive novel therapeutic option that may allow for a moderate reduction in platelet activation and decreased thrombosis while still permitting the primary hemostatic function of platelet plug formation.